Romanian Professional Accountants' Perception on the Differential Financial Reporting for Small and Medium-Sized Enterprises - Stefan Bunea; Marian Sacarin; Mihaela Minu (Journal of Accounting and Management Information Systems (JAMIS), 2012)
2009 was an important year, internationally, for the financial reporting of small and medium-sized enterprises. First of all, the International Accounting Standards Board (IASB) published the International Financial Reporting Standard for the Small and Medium–Sized Entities (IFRS for SMEs). Secondly, the European Commission started the consultations over the amendment of the 4th and 7th Directives with a view to simplifying them for the small entities. Moreover, the European Commission launched a consultation over a possible adoption of the IFRS for SMEs at the level of the European Union. Through our study we attempt mainly to identify the attitude of Romanian professional accountants about the financial reporting of the small and medium-sized enterprises (SMEs). Data was collected through questionnaires on a sample of 190 accountants. The results indicate that more than a half of respondents consider that the current regulations do not provide a reasonable level of simplification for SMEs and, consequently, a more simplified reporting system is needed for these entities. However, only very few respondents consider than the IFRS for SMEs in its current form is adequate. It was found that respondents having an experience of up to 10 years reject more willingly the idea of detailed rules and accept the need for professional judgment. Besides capturing the accountants' attitude towards the IFRS for SMEs, our study identifies the main users of accounting information prepared by SMEs. Besides contributing to a scarce literature on the IFRS for SMEs applicability, these results are useful for practitioners and regulators when considering the change in the regulations for SMEs.
Keywords: M41; 650; Differential reporting; small and medium-sized enterprises (SMEs); professional accountants; IFRS for SMEs; European directives